INTEGRATING THE MORAL EDUCATIONAL THOUGHT OF CLASSICAL ISLAMIC SCHOLARS INTO THE CONTEMPORARY ISLAMIC RELIGIOUS EDUCATION CURRICULUM - Alhamuddin, Alhamuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
This study explored the integration of classical Islamic scholars’ (ulama) moral educational thought into the development of contemporary Islamic education curricula. The research was motivated by the concern that current Islamic Religious Education often emphasized cognitive aspects while overlooking the ethical and character-building dimensions deeply rooted in Islamic tradition. Using a qualitative-descriptive approach, the study analyzed selected classical texts by prominent ulama such as Al-Ghazali, Ibn Miskawayh, and Ibn Khaldun, focusing on their concepts of moral education, character formation, and the philosophical foundations of ethics in learning. The findings showed that their thoughts provided valuable insights for constructing a holistic curriculum that balanced knowledge, spirituality, and character. The study revealed that integrating classical moral philosophy enriched curriculum content, pedagogical approaches, and evaluation models in contemporary Islamic education. The discussion emphasized the significance of reconnecting with Islamic intellectual heritage to establish a value-based education that responded to modern educational challenges. This research contributed theoretically to curriculum development and advocated for a culturally rooted and morally grounded educational paradigm.